Junior ice hockey players` special physical fitness tests: update options - Kuzmenko, A. A.; Kim, T. K.; Kuzmenko, G. A. (Theory and Practice of Physical Culture, 2019)
The article analyzes the validity and dependability of the standard test toolkit to rate special physical fitness of junior (9-10 year-old) ice hockey players trained at the National Ice Hockey Center (Moscow). Having analyzed the standard test toolkit for its update purposes, we found the speed rating test tools excessive and the motor coordination rating test tools insufficient. The players were tested with the poor decision-making skills under time pressure in the high-speed and coordination-intensive game situations. The existing toolkit was recommended to be updated to include new decision-making ability rating test tools, with the performance rated by the `fast+ accurate` and `fast+ successful` rates. The high correlations of the test tools require the toolkit being complemented by the tests of modern competitive skills and their combinations, with the tests being particularly sensitive to the movement coordination qualities and abilities. Relatively low correlations were found for the following tests: puck-free 36m forward skating skills test; 17/4m sprint test; and the 6x9m puck-free shuttle sprint test. The body weight ratio was found to be in positive correlation with the puck-free 36m forward skating skills due to the natural inertial aspects; and in negative correlations with the 1-17m forward sprint skills - indicative of the lower body weight ratio indices favoring the speed and movement control qualities. The study also found that some tests may be clustered to secure the test process relevance and versatility: thus the reverse skating speed test was found highly valuable and informative for the coordination and physical qualities and skills rating in the junior players` special physical fitness rating test toolkit.